Whatever does not kill us: cumulative lifetime adversity, vulnerability, and resilience - Seery, Mark D; Holman, E Alison; Silver, Roxane Cohen (Journal of personality and social psychology, 2010)
Exposure to adverse life events typically predicts subsequent negative effects on mental health and well-being, such that more adversity predicts worse outcomes. However, adverse experiences may also foster subsequent resilience, with resulting advantages for mental health and well-being. In a multiyear longitudinal study of a national sample, people with a history of some lifetime adversity reported better mental health and well-being outcomes than not only people with a high history of adversity but also than people with no history of adversity. Specifically, U-shaped quadratic relationships indicated that a history of some but nonzero lifetime adversity predicted relatively lower global distress, lower self-rated functional impairment, fewer posttraumatic stress symptoms, and higher life satisfaction over time. Furthermore, people with some prior lifetime adversity were the least affected by recent adverse events. These results suggest that, in moderation, whatever does not kill us may indeed make us stronger.